FRICTIONAL CONTACT STRESS ANALYSIS Of SPUR AND HELICAL GEARS - SHARANAGOUDA PATIL, SANTOSH (2015)
Gears are one of the most crucial components in mechanical power transmission systems. The bending and surface stresses of the gear tooth are considered to be one of the main contributors of the failure of gears. Thus, stress analysis of gears has become a popular area of research to minimize or to reduce the failures and to optimize the design of gears. This thesis investigates the characteristics of an involute spur and helical gear systems mainly focusing on contact stresses, using infinite element analysis. A few cases of gear system were using analytical and experimental method for validation purposes.